Pathogenic functions of B cells in autoimmune diseases: IFN‐γ production joins the criminal gang. Issue 4 (April 2015) - Fillatreau, Simon
<x xml:space="preserve">Abstract</x> B‐cell depletion therapy has emerged as a powerful strategy to intercept the progression of T‐cell‐mediated autoimmune diseases such as rheumatoid arthritis, type 1 diabetes, or relapsing remitting multiple sclerosis. However, its mode of action remains incompletely defined, reflecting our incomplete understanding of the pathogenic functions of B cells in such pathologies. B cells can contribute to immune responses through the production of antibodies, presentation of antigen to T cells, and production of cytokines. In this issue of the European Journal of Immunology [Eur. J. Immunol. 2015. 45: 988–998], Olalekan et al. demonstrate that IFN‐γ production by B cells is essential for the development of arthritis in mice. Lack of IFN‐γ expression in B cells results in reduced autoimmune T‐cell responses and autoantibody levels, impacting the arthritogenic reaction akin to that in B‐cell depletion therapy. Together with other reports, the article by Olalekan et al. emphasizes the importance of cytokine‐producing B cells in the pathogenesis of autoimmune diseases. In this commentary, I discuss how these findings shed new light on the roles of B cells as drivers of autoimmune pathogenesis, and how they more generally contribute to our understanding of the role of B cells in immunity.